The study of customers' acceptance towards Felda Prodata Systems Sdn Bhd inbound marketing programs in Kuala Lumpur / Che Zuren Yusrena Che Yussof - Che Yusoff, Che Zuren Yusrena (2012)
The aim of this study was to examine the factors that influencing customers’ acceptance towards Felda Prodata Systems Sdn Bhd inbound marketing programs in Kuala Lumpur. There are five factors that been studied, which were perceived usefulness, perceived ease to use, trust, perceived enjoyment and attitude toward using. The objective of this study is to see the important factors that influence customers’ acceptance towards inbound marketing programs. Then, the findings of this study will be beneficial to Felda Prodata in ensuring its acceptance to inbound marketing programs. Data were gathered from the questionnaires which were distributed to 160 respondents of Felda Prodata customers who are using their products and services. The data were analyzed using Statistical Procedure of Social System (SPSS) through the frequencies analysis, mean analysis, and correlation coefficient analysis. Based on the results obtained in this study, the researcher found out that four from five independent variables used in this study are significant towards the dependent variable of the study. The variables are perceived ease to use, perceived usefulness, trust, and attitude towards using. Moreover, the researcher has derived one model using regression analysis for this study. The researcher suggests some recommendations such as royalty programs, to have flexible interaction, and engagement programs that can help Felda Prodata to assist the current and future potential sales